Structural connectome gradients and their relationship to IQ in childhood - Hong, Yoonmi; Cornea, Emil; Girault, Jessica B.; Stephens, Rebecca L.; Bagonis, Maria; Foster, Mark; Kim, Sun Hyung; Prieto, Juan Carlos; Styner, Martin A.; Gilmore, John H. (Frontiers in Human Neuroscience, 2025)
The concept of connectome gradients, which represents the continuous spatial variation of brain connectivity, offers a robust framework for exploring the hierarchical organization of the cortex and its relationship with cognitive function. We hypothesize that structural gradients in frontal and parietal regions play a significant role in shaping individual cognitive abilities during early childhood. To evaluate this hypothesis, we identified macroscale structural connectome gradients in children aged 1–6 years, where the principal gradient exhibited a left-to-right axis, and the secondary gradient exhibited an anterior-to-posterior axis. Next, we employed machine learning approaches to predict the future cognitive outcomes assessed at ages 4, 6, and 8, specifically intelligence quotient (IQ), based on the structural connectome gradients measured at age 1. We achieved consistent and robust prediction results (mean Spearman's correlation > 0.25). The regional relevance maps highlighted regions in control network, and associated sensory processing networks. Our findings indicate that the structural connectome, which undergoes maturation during early childhood, plays a crucial role in the individual variability of IQ observed in early and middle childhood. Our approach underscores the utility of structural gradients as compact and interpretable representations of the brain's complex network architecture, effectively capturing individual differences that contribute to cognitive development.